Functional Domains of the Early Proteins and Experimental and Epidemiological Studies Suggest a Role for the Novel Human Polyomaviruses in Cancer - Moens, Ugo; Prezioso, Carla; Pietropaolo, Valeria (Frontiers in Microbiology, 2022)
As their name indicates, polyomaviruses (PyVs) can induce tumors. Mouse PyV, hamster PyV and raccoon PyV have been shown to cause tumors in their natural host. During the last 30 years, 15 PyVs have been isolated from humans. From these, Merkel cell PyV is classified as a Group 2A carcinogenic pathogen (probably carcinogenic to humans), whereas BKPyV and JCPyV are class 2B (possibly carcinogenic to humans) by the International Agency for Research on Cancer. Although the other PyVs recently detected in humans (referred to here as novel HPyV; nHPyV) share many common features with PyVs, including the viral oncoproteins large tumor antigen and small tumor antigen, as their role in cancer is questioned. Here, we review the current knowledge that argues for or against a role of these nHPyVs in cancer and suggest future studies that may help to clarify their possible involvement in human malignancies.